Analysis of the deployment scale and investment prediction of China’s coal power carbon capture technology under typical scenarios before 2050 - Jianfang Zong; Qing Ding; Haitao Wang; Xinyu Cao; Jie Wei (PLoS ONE, 2025)
This study evaluates the potential for green and low-carbon transformation in China’s coal-fired power sector by analyzing seven representative scenarios, including projections for total installed capacity, power generation, and coal-fired power metrics before 2050. Carbon emissions are estimated using a conversion factor of 0.899 kg CO₂ per kWh, while deployment scales and emission reduction potentials for carbon capture technologies are calculated based on IEA (2022) assumptions for low (30%) and high (90%) installation ratios. The study further quantifies installation and operational costs, investment requirements by 2050, and annual investments from 2030 to 2050 under both scenarios. Results demonstrate that high-proportion carbon capture deployment can significantly accelerate the sector’s low-carbon transition, fostering an emerging industry worth over 20 trillion yuan and delivering dual benefits of emissions reduction and economic growth. Policy support for large-scale implementation is critical. By pioneering multi-scenario modelling, this research systematically projects China’s coal-fired CCUS deployment needs under 1.5°C and 2°C climate targets, integrating IEA frameworks with domestic policy scenarios to assess industrial-scale potential and inform decision-making. This work provides the first systematic integration of IEA projections with China-specific policy scenarios, offering policymakers a framework to balance climate targets with energy transition realities.